Answer:
The zeros of given expression [tex] -x^3-3x^2=6x+4[/tex] is -1, [tex]-1+i\sqrt{3}[/tex] and [tex]-1-i\sqrt{3}[/tex]
Step-by-step explanation:
Given expresssion is [tex]-x^3-3x^2=6x+4[/tex]
To find zeros of given expression we have to equate the expression to zero.
ie., [tex]-x^3-3^2-6x-4=0[/tex]
[tex]-(x^3+3x^2+6x+4)=0[/tex]
[tex]x^3+3x^2+6x+4=0[/tex]
By using synthetic division
-1 | 1 3 6 4
| 0 -1 -2 -4
|________________
1 2 4 0
Therefore (x+1) is a zero
Now the quadratic equation is [tex]x^2+2x+4=0[/tex]
For quadratic equation [tex]ax^2+bx+c=0[/tex] we have
[tex]x=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
Here a=1 ,b=2 and c=4 now substitute the values
[tex]x=\frac{-2\pm \sqrt{2^2-4(1)(4)}}{2(1)}[/tex]
[tex]x=\frac{-2\pm \sqrt{4-16}}{2}[/tex]
[tex]x=\frac{-2\pm \sqrt{-12}}{2}[/tex]
[tex]x=\frac{-2\pm \sqrt{12i^2}}{2}[/tex] where [tex]i^2=-1[/tex]
[tex]x=\frac{-2\pm i \sqrt{4\times 3}}{2}[/tex]
[tex]x=\frac{-2\pm i \sqrt{4}\sqrt{3}}{2}[/tex]
[tex]x=\frac{-2\pm 2i\sqrt{3}}{2}[/tex]
[tex]x=2\times\frac{(-1\pm i\sqrt{3})}{2}[/tex]
[tex]x=-1\pm i\sqrt{3}[/tex]
Therefore [tex]x=-1+i\sqrt{3}[/tex] and [tex]x=-1-i\sqrt{3}[/tex]
Therefore the zeros are -1, [tex]-1+i\sqrt{3}[/tex] and [tex]-1-i\sqrt{3}[/tex]